Combination chemotherapy and hormone therapy in patients with hormone receptor positive and HER2 negative metastatic breast cancer - Kripa Bajaj; Sushmita Rath; Deep Vora; Pallavi Parab; Seema Gulia; Swapnil Rane; Tanuja Shet; Jaya Ghosh; Palak Popat; Prabhat Bhargava; Anbarasan Sekar; Anuradha Mehta; et al. (Scientific Reports)
Abstract There is sparse data on the outcomes of combined chemotherapy and hormonal therapy (CHT) in patients with metastatic breast cancer (MBC). This retrospective analysis of HR-positive, HER2-negative MBC patients treated between January 2015 and December 2020 with a combination of chemotherapy (capecitabine or oral cyclophosphamide) and hormonal therapy evaluated their progression-free survival (PFS) and overall survival (OS).The study included 224 patients with a median age of 53 (26–91) years, a median of 3 (0–12) prior treatment lines and a median follow-up of 21.2 (1.7–87.0) months. There were 195 (87.1%) PFS events and 154 (68.8%) deaths, with a median PFS of 8.8 (95% CI 7.0-10.6) months and a median OS of 16.7 (95% CI 13.5–19.9) months. In univariable analyses, ECOG PS (≤ 1 vs. ≥ 2, PFS 14.9 vs. 6.0 months, HR 0.32, 95% CI 0.23–0.44, p < 0.001; OS 36.2 vs. 11.0 months, HR 0.29, 95% CI 0.20–0.42, p < 0.001) and duration of most recent endocrine therapy (> 12 vs. ≤ 12 months, PFS 11.7 vs. 6.9 months, HR 0.32, 95% CI 0.23–0.44, p = 0.023; OS 21.9 vs. 15.0 months, HR 0.70, 95% CI 0.49–0.99, p = 0.047) were significantly associated with survival. In multivariable Cox analyses, better ECOG PS (HR 0.29, 95% CI 0.19-0.43, p<0.001) and capecitabine-based chemotherapy (HR 0.60, 95% CI 0.37-0.99, p=0.043) were significantly associated with higher OS. The chemo-hormonal therapy regimens were well tolerated, with 21 (9.4%) patients experiencing any grade ≥3 toxicity. Chemo-hormonal therapy is an effective treatment in heavily pre-treated MBC patients, including those with visceral metastases. Trial registration: CTRI/2022/01/039242